The magnetic field and the evolution of element spots on the surface of the HgMn eclipsing binary AR Aur - Hubrig, S. (2010)
The system AR Aur is a young late B-type double-lined eclipsing binary with a primary star of HgMn peculiarity. We applied the Doppler imaging method to reconstruct the distribution of Fe and Y over the surface of the primary using spectroscopic time series obtained in 2005 and from 2008 October to 2009 February. The results show a remarkable evolution of the element distribution and overabundances. Measurements of the magnetic field with the moment technique using several elements reveal the presence of a longitudinal magnetic field of the order of a few hundred gauss in both stellar components and a quadratic field of the order of 8 kG on the surface of the primary star.